Czy Adolf Hitler był katechonem? Uwaga na marginesie dyskusji o istocie teologii politycznej Carla Schmitta - Wielomski, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The paper puts forward the hypothesis that Carl Schmitt’s flirting with National Socialism and the Third Reich was not motivated by opportunistic factors. He was also not influenced by purported ideological closeness, as is sometimes suggested by scholars of either left-wing or Fascist orientation. The author proposed a hypothesis that Carl Schmitt gave his support to Adolf Hitler because, writing contemporaneous political events and occurrences into his political theology, he considered Hitler to be the katechon from Saint Paul’s Second Epistle to the Thessalonians. Although extremely interested in this issue, Schmitt never explicitly wrote who or what the katechon is. Therefore the hypothesis cannot be proven beyond any doubt. Nevertheless, the gathered material indicates that such an interpretation is both possible and credible. During the 1933–1947 period Hitler was perceived by Schmitt as the katechon. The indirect support for this hypothesis is provided by numerous clues left by the German jurist, and also by various contexts in which his considerations on the concept of katechon appeared. Schmitt’s self-accounting with National Socialism became possible only in 1948 when he realized that the Catholic Church is the true katechon and that the Third Reich had been led by the Antichrist.
Keywords: Hitler, Adolf (1889-1945); Schmitt, Carl; teologia polityczna; katechon; narodowy socjalizm